Step-by-step smelting method for Ti-based hydrogen storage alloy

Through the step-by-step smelting method, the initial smelting of the elements on the Zr and B side of the sponge are first performed, and then the sponge Ti is added for rapid melting, which solves the problems of small preparation scale, long smelting time and poor performance stability of Ti-based hydrogen storage alloy, and achieves high efficiency , stable alloy preparation.

CN119464786APending Publication Date: 2025-02-18INST OF RESOURCES UTILIZATION & RARE EARTH DEV GUANGDONG ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411393631.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The Ti-based hydrogen storage alloy has a small preparation scale, a long smelting time and poor performance stability. It is mainly due to the inducible heating of the sponge Ti and the large volume, which leads to the "bridge building" phenomenon and the low initial smelting power.

Method used

Using step-by-step smelting method, first place the sponge Zr and the B-side element that is easily induced in the induction crucible for the first stage of smelting. After the metal is melted, then add sponge Ti for the second stage of smelting, so as to achieve rapid melting of sponge Ti and Evenly distributed.

Benefits of technology

The preparation scale and smelting efficiency of Ti-based hydrogen storage alloy are significantly improved, the smelting time is shortened, the stability of alloy performance is improved, and the service life of the smelting crucible is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464786A_ABST
    Figure CN119464786A_ABST
Patent Text Reader

Abstract

The invention discloses a Ti-based hydrogen storage alloy step-by-step smelting method which comprises the following steps: placing sponge Zr in an induction crucible, then placing an easily inducted B side element for first-stage smelting, after metal in the crucible is melted, adding sponge Ti, sinking the sponge Ti in molten metal and quickly melting, and performing second-stage smelting to obtain the Ti-based hydrogen storage alloy. The Ti-based hydrogen storage alloy has the advantages of being large in smelting amount, rapid in smelting and good in performance stability. In addition, due to the fact that the smelting time of the Ti-based hydrogen storage alloy is greatly shortened, long-time overheating of the bottom of the crucible is avoided, and the service life of the smelting crucible can be effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of alloy smelting, and in particular to a method for step-by-step smelting of a Ti-based hydrogen storage alloy. Background technology:

[0002] At present, hydrogen, as a clean and efficient renewable energy, has become the direction of change in a new round of energy technology. Ti-based hydrogen storage alloys have the advantages of high hydrogen storage capacity, low cost, and good hydrogen absorption / release platform characteristics. They are expected to become hydrogen storage alloys that can be industrialized after rare earth-based LaNi5 hydrogen storage alloys. Ti-based hydrogen storage alloys are composed of hydrogen absorption elements (Ti and Zr) on the A side and performance adjustment elements (Mn, Cr, Fe, V, Ni, Cu and La, etc.) on the B side. There are mainly two types of hydrogen storage alloys, Ti-Mn-V-Fe and Ti-Zr-Cr-Fe. In order to reduce the cost of the alloy, Ti and Zr in the charge are replaced by sponge Ti and sponge Zr, while V is replaced by 80VFe (vanadium-iron alloy containing about 80wt% V).

[0003] Medium frequency induction melting method has the advantages of low production cost, simple operation and large production batch, and is the main production method of hydrogen storage alloy. At present, this method has been successfully applied to the large-scale preparation of rare earth-based LaNi5 hydrogen storage alloy materials. However, since the melting temperature of Ti-based hydrogen storage alloys (1600-1800°C) is significantly higher than that of rare earth-based hydrogen storage materials (~1200°C), medium frequency induction melting method has not yet been fully successfully used for mass production of Ti-based hydrogen storage alloys.

[0004] In Ti-based hydrogen storage alloys, the melting points of the A-side elements are relatively high (Ti: 1668°C, Zr: 1885°C), while the melting points of the B-side elements are relatively low (Mn: 1246°C, Fe: 1538°C, Ni: 1455°C, La: 920°C, Cu: 1085°C, except for Cr and V, both of which have melting points close to 1910°C). In a medium-frequency induction melting furnace, the electromagnetic induction intensity in the middle and lower parts of the crucible is relatively high, which is suitable for placing materials with high melting points. Therefore, the conventional method for preparing Ti-based hydrogen storage alloys is: sponge Ti (and a small amount of sponge Zr) is placed at the bottom, and the B-side block metal with a lower melting point and easy to sense is placed on top.

[0005] The melting process of Ti-based hydrogen storage alloy is divided into three steps: "heating - melting - falling". First, the bottom alloy charge heats up and softens, and welds to form a large block of molten metal; then, when the induced eddy current is large enough, the molten metal block melts into liquid metal and accumulates at the bottom of the crucible; finally, the remaining charge gradually softens and falls into the liquid metal to melt (see Figure 1 ). At present, the above method can prepare a small amount of Ti-based hydrogen storage alloy (charge ≤ 7kg) in a 25kg melting furnace. However, in the continued expansion of pilot tests, the smelting of Ti-based hydrogen storage alloys encountered the following problems:

[0006] 1. Small scale of preparation. Since the materials of Ti-based hydrogen storage alloy are mostly irregular small particles with low bulk density, the crucible of a 25kg melting furnace can only load 7kg of materials at most, otherwise the upper layer of materials will not be effectively softened by heat and fall off, forming a "bridging" phenomenon.

[0007] 2. Long melting time: The initial melting power is low and the heating rate is slow. Usually, when loading 7kg of charge, the starting power is 18kW, which slowly rises to 20kW after 10 minutes, and the power rises to 36kW after about 40 minutes. The bottom metal melts and enters the rapid melting stage. It will take another 20 minutes for the remaining charge to fall and melt. Adding 5 minutes of insulation time, the total melting time exceeds 60 minutes.

[0008] 3. Poor performance stability: Due to the complex composition of alloy charge, different melting order, and large deviation in smelting time, the volatilization amount of each alloy component is inconsistent, resulting in alloy performance deviation. In particular, the emergence of the "bridging" phenomenon will cause the composition to deviate from the original formula, seriously affecting the stability of the performance of Ti-based hydrogen storage alloys between batches.

[0009] As the main component of Ti-based hydrogen storage alloy, Ti accounts for 20-30% of the total mass and plays an important role in alloy smelting. 3 ), its volume often accounts for more than 50% of the total volume, affecting the loading capacity of the charge. At the same time, due to the small particles, large gaps and large space occupied by sponge Ti, the induced eddy current is small, the initial smelting power is low, and the smelting time is long. In addition, since sponge Ti occupies a large space, a long air layer is formed above it after it melts, resulting in the upper charge not being able to effectively soften by heat and falling off, forming a "bridging" phenomenon. Therefore, sponge Ti is the main reason for the small scale of preparation of Ti-based hydrogen storage alloys, long smelting time and poor performance stability. How to reasonably place these sponge Ti that are not easy to be inductively heated and occupy volume is a key issue that needs to be solved for the batch preparation of Ti-based hydrogen storage alloys. Summary of the invention:

[0010] The purpose of the present invention is to provide a method for stepwise smelting of a Ti-based hydrogen storage alloy, which solves the problems of small preparation scale, long smelting time and poor performance stability of the Ti-based hydrogen storage alloy in the prior art.

[0011] The present invention is achieved through the following technical solutions:

[0012] A method for step-by-step smelting of a Ti-based hydrogen storage alloy comprises the following steps: firstly placing sponge Zr and an easily induced B-side element in an induction crucible for first-stage smelting, and then adding sponge Ti for second-stage smelting after the metal in the crucible is melted. At this time, the sponge Ti sinks in the molten metal and melts quickly, which can effectively solve the problems of small preparation scale, long smelting time and poor performance stability, and significantly improve the production efficiency of the Ti-based hydrogen storage alloy.

[0013] The Ti-based hydrogen storage alloy includes two types of hydrogen storage alloys, namely Ti-Mn-V-Fe series and Ti-Zr-Cr-Fe series. Based on the total mass percentage of 100%, the components are Ti: 20-30%, Zr: 5-20%, Cr: 5-30%, Mn: 5-45%, Fe or 80VFe: 20-25%, and the rest are a small amount of Ni, Cu and La.

[0014] The easily induced B-side elements include Cr, Mn, Ni, Cu, La, Fe or 80VFe.

[0015] The specific steps include:

[0016] 1) Weigh the Ti-based hydrogen storage alloy charge according to the formula, and place the sponge Ti aside for later use.

[0017] 2) Feeding: Place the sponge Zr and the B-side elements that are easy to sense and have a lower melting point in an induction crucible to prepare for smelting;

[0018] For Ti-Mn-V-Fe series hydrogen storage alloys, place sponge Zr first, then Cr, Mn, Ni, Cu, La in sequence, and finally Fe; for Ti-Zr-Cr-Fe series, place sponge Zr first, then Cr, 80VFe and Mn in sequence, and finally Ni, Cu, La.

[0019] 3) Preheating: Preheat at 7 kW and 14 kW for 1 minute respectively.

[0020] 4) First stage smelting: the input power is adjusted to the maximum, and after 4-8 minutes, the power rises to 36kW, the bottom metal melts, and the power is maintained at 35-36kW until the remaining charge in the crucible falls and melts, which takes 9-11 minutes.

[0021] 5) Second stage smelting: slowly add sponge Ti through the feeding mechanism, which takes 1-3 minutes, and keep warm at 36kW for 5 minutes to make all the alloy melted and uniform.

[0022] The appropriate amount of sponge Zr and B-side elements and other charges is between 1 / 4 and 3 / 4 of the crucible volume.

[0023] The beneficial effects of the present invention are as follows: the present invention has the advantages of large melting amount, fast melting and good performance stability of Ti-based hydrogen storage alloy. In addition, since the melting time of Ti-based hydrogen storage alloy is greatly reduced, the crucible is prevented from overheating for a long time, and the service life of the melting crucible is effectively extended. Description of the drawings:

[0024] Figure 1 It is a schematic diagram of the one-step melting process of the existing technology of Ti-based hydrogen storage alloy;

[0025] Figure 2 It is a schematic diagram of the step-by-step smelting process of the Ti-based hydrogen storage alloy of the present invention;

[0026] Figure 3 The PCT performance diagram of SA-02 alloy prepared by one-step smelting (left) and step-by-step smelting (right) in Example 1;

[0027] Figure 4 It is a comparison chart of the smelting time of preparing SA-02 alloy by one-step smelting and step-by-step smelting in Example 1;

[0028] Figure 5 The PCT performance diagram of 8, 10, 12 and 14 kg SA-04 alloys prepared by the step-by-step smelting method in Example 2;

[0029] Figure 6 This is a PCT comparison chart of 8 kg (left) and 120 kg (10 furnaces) (right) SA-04 alloy prepared by the step-by-step smelting method in Example 2. Specific implementation method:

[0030] The following is a further description of the present invention, rather than a limitation of the present invention.

[0031] Example 1: Preparation of Ti-Mn-V-Fe SA-02 Hydrogen Storage Alloy by Different Methods

[0032] SA-02 alloy is a Ti-based hydrogen storage alloy used in solid-state hydrogen storage systems. Its composition is 25-30% Ti, 5-10% Zr, 5-10% Cr, 40-45% Mn, 20-25% 80VFe, and a small amount of Ni, Cu and La. In order to verify the feasibility of the step-by-step smelting method, 7kg of SA-02 alloy was prepared by conventional method (one-step smelting method) and step-by-step smelting method, and its PCT performance was tested for comparison.

[0033] The conventional method (one-step smelting method) for preparing SA-02 hydrogen storage alloy comprises the following steps:

[0034] Weighing: weigh 7kg of alloy charge according to the formula, of which sponge Ti is placed separately for standby use.

[0035] Feeding: Place sponge Ti and Zr at the bottom of the crucible, then put Cr, 80VFe and Mn in sequence, and finally put Ni, Cu and La.

[0036] Preheating: Preheat at 7kW and 14kW for 1 minute.

[0037] Heating and melting: Adjust the input power to the maximum, and it takes 40 minutes for the power to rise to more than 36kW, and the metal at the bottom melts. Keep the power at around 36kW, and wait for the remaining charge to fall and melt, which takes 25 minutes. Keep the temperature for 5 minutes to make all the alloy melt and even.

[0038] The method for stepwise smelting of the SA-02 hydrogen storage alloy comprises the following steps:

[0039] Weighing: weigh 8kg of alloy charge according to the formula, of which sponge Ti is placed separately for standby use.

[0040] Feeding: Place Zr sponge at the bottom of the crucible, followed by Cr, 80VFe and Mn, and finally Ni, Cu and La.

[0041] Preheating: Preheat at 7kW and 14kW for 1 minute.

[0042] First stage of melting: The input power is adjusted to the maximum, and it takes 8 minutes for the power to rise to more than 36kW, and the metal at the bottom melts. The power is maintained at around 36kW, and the remaining charge falls and melts, which takes 10 minutes.

[0043] Second stage of melting: slowly add sponge Ti through the feeding mechanism, which takes 2 minutes. Keep warm for 5 minutes to make all the alloy melted and uniform.

[0044] Figure 3 This is the PCT performance diagram of SA-02 alloy prepared by one-step smelting and step-by-step smelting. Figure 3 It can be seen that the hydrogen storage capacity of the SA-02 alloy prepared by the two methods is basically the same (1.81 and 1.82wt%), while the hydrogen absorption / desorption platform of the alloy prepared by the step-by-step smelting method is slightly lower (7.50 / 3.45 and 6.48 / 3.21atm).

[0045] Figure 4 It is the melting time of SA-02 alloy prepared by one-step melting and step melting. Figure 4 It can be seen that the step-by-step smelting method can significantly reduce the smelting time of the alloy. The time of the step-by-step smelting method is 8+12+5=25 minutes, while the smelting time of the one-step smelting method is 40+25+5=70 minutes. The time of the step-by-step smelting method is only 36% of that of the one-step smelting method.

[0046] It can be seen that the step-by-step smelting method successfully prepared the Ti-based hydrogen storage alloy, broke through the limitation of smelting amount (≤7kg), and greatly reduced its smelting time.

[0047] Example 2: Large-scale preparation of Ti-Zr-Cr-Fe SA-04 alloy

[0048] SA-04 is a Ti-based hydrogen storage alloy used in static hydrogen compression systems. Its composition is 20-25% Ti, 15-20% Zr, 25-30% Cr, 5-10% Mn, 20-25% Fe, and a small amount of Ni, Cu and La. In order to verify the effect of step-by-step smelting on improving production batch and stability, SA-04 alloys of different qualities were prepared by step-by-step smelting, and their PCT performance was tested for comparison.

[0049] The method for stepwise smelting of the SA-04 hydrogen storage alloy comprises the following steps:

[0050] Weighing: According to the formula, weigh 8, 10, 12 and 14 kg of Ti-based hydrogen storage alloy charges, of which sponge Ti is placed separately for standby use.

[0051] Feeding: Place Zr sponge at the bottom of the crucible, then place Cr, Mn, Ni, Cu and La in sequence, and finally Fe.

[0052] Preheating: Preheat at 7kW and 14kW for 1 minute.

[0053] The first stage of melting: the input power is adjusted to the maximum, and it takes 8 minutes to heat up to 36kW and enter the rapid melting stage. The more the charge, the faster the heating rate. The remaining charge in the crucible falls and melts, which takes 10 minutes.

[0054] Second stage of melting: slowly add sponge Ti through the feeding mechanism, which takes 2 minutes. Keep warm for 5 minutes to make all the alloy melted and uniform.

[0055] Figure 5 The PCT performance diagram of 8, 10, 12 and 14 kg SA-04 alloys prepared by step melting method. Figure 5 It can be seen that the step-by-step smelting method significantly improves the batch preparation amount while maintaining the PCT performance of the alloy. Compared with the conventional method (one-step smelting method, see Example 1) smelting 7kg smelting amount, the step-by-step smelting method can achieve a maximum smelting amount of 14kg, and the efficiency is improved by 100%.

[0056] Figure 6 This is a PCT comparison chart of 8kg and 120kg (10 furnaces) of SA-04 alloy prepared by step melting method. Figure 6It can be seen that the performance of the 120kg mixed sample is basically the same as that of the 8kg sample, which proves the performance stability of the Ti-based hydrogen storage alloy prepared by the step-by-step smelting method. Therefore, the step-by-step smelting method can efficiently and stably prepare SA-04 alloy.

[0057] In addition, the SA-04 alloy was prepared by the step-by-step smelting method, with a yield rate of over 90% and a crucible life of over 30 furnaces. However, the conventional method for preparing Ti-based hydrogen storage alloys with similar formulas has a yield rate of about 50% and a crucible life of only about 20 furnaces due to the unstable smelting time.

Claims

1. A low-iridium oxygen evolution membrane electrode for a proton exchange membrane water electrolyzer, characterized in that: The catalytic layer is composed of a preformed porous metal conductive thin layer and an iridium-based and / or ruthenium-based catalyst loaded on the surface thereof. The preformed porous metal conductive thin layer is formed by coating or spraying acid-corrosion-resistant metal powder and a binder on the surface of a polytetrafluoroethylene film and then drying. The iridium-based and ruthenium-based catalysts are metals or metal oxides or metal hydroxides of iridium or ruthenium, with a particle size of 1 to 50 nm and an iridium or ruthenium loading of 0.04 to 0.2 mg / cm -2 .

2. The low-iridium oxygen evolution membrane electrode for proton exchange membrane water electrolyzer according to claim 1, characterized in that: Iridium or ruthenium loading is 0.04-0.1mgcm -2 .

3. The low iridium oxygen evolution membrane electrode for proton exchange membrane water electrolyzer according to claim 1, characterized in that: The metal powder is one or a combination of gold, titanium and niobium, and the particle size of the metal powder is 0.06-5 μm.

4. The low iridium oxygen evolution membrane electrode for proton exchange membrane water electrolyzer according to claim 3, characterized in that: The particle size of the metal powder is 0.3-2 μm.

5. The low-iridium oxygen evolution membrane electrode for proton exchange membrane water electrolyzer according to claim 1, characterized in that: The binder is polytetrafluoroethylene or perfluorosulfonic acid resin, and the content of the binder is 1%-20%.

6. The low-iridium oxygen evolution membrane electrode for proton exchange membrane water electrolyzer according to claim 1, characterized in that: The iridium-based and ruthenium-based catalysts are loaded in chemical deposition, electrodeposition, impregnation reduction, impregnation sintering, and ink spraying methods.

7. The low-iridium oxygen evolution membrane electrode for proton exchange membrane water electrolyzer according to claim 1, characterized in that: The thickness of the porous metal conductive thin layer is 0.1-10 μm.

8. A method for preparing a low-iridium oxygen evolution membrane electrode for a proton exchange membrane water electrolyzer according to claim 1, characterized in that: The following steps are involved: (1): Mix metal powder with water and ethanol, then add a binder, wherein the binder content is 1% to 20%, and mix evenly by ultrasonic stirring to obtain a metal powder mixed solution; use a coating or spraying process to cover the metal powder mixed solution on the surface of the polytetrafluoroethylene film, control the thickness of the thin layer by adjusting the coating amount of the metal powder mixed solution, and then dry to form a porous metal conductive thin layer; (2) placing the porous metal conductive thin layer coated on the surface of the tetrafluoroethylene film obtained in step (1) in a chloroiridic acid or / and ruthenium trichloride precursor solution, and then forming an iridium-based and / or ruthenium-based metal or metal oxide or metal hydroxide on the surface of the porous metal conductive thin layer by chemical deposition or electrochemical deposition or impregnation reduction or impregnation sintering to obtain a porous metal conductive thin layer loaded with an iridium-based and / or ruthenium-based catalyst; Or, by preparing an ink of iridium oxide and / or ruthenium oxide, and spraying the ink onto the surface of a porous metal conductive thin layer coated on the surface of a tetrafluoroethylene film to achieve loading; (3) The porous metal conductive thin layer loaded with iridium-based and / or ruthenium-based catalyst obtained in step (2) is transferred to the surface of the proton exchange membrane by a transfer method to form a low-iridium anode.

9. The preparation method according to claim 8, characterized in that: The metal powder is one or a combination of gold, titanium and niobium, and the particle size of the metal powder is 0.06-5 μm; the binder is polytetrafluoroethylene or perfluorosulfonic acid resin.

10. The preparation method according to claim 8, characterized in that: The thickness of the porous metal conductive thin layer is 0.1-10 μm.